Use of farmer recall versus direct measurement in gathering lactation data: Lessons from Kenyan smallholder dairy systems - Staal, Steven J.; Omore, Amos O. (British Society of Animal Science, 1998)
The use of farmer-recall in field data collection typically allows for relatively quick and low-cost information gathering. Such data can often be gathered using a simple cross-sectional survey, in many cases requiring only a single farm visit. In return, however, there may be an increase in measurement error and a decrease in the quality of the data in general, due to recall-error and lack of an established relationship between enumerator and respondent. More accurate data can only be gathered by direct measurement methods, and may require repeated farm visits to capture effects of seasonality or periodicity. The cost of using recall data in terms of reduced reliability of research results, however, may be reduced when there is a high degree of natural variability in the data. Under such circumstances, for example when gathering data for the estimation of lactation curves of cows on smallholder tropical farms where feed resources are poor and highly variable, the additional effort and cost of recording milk yields over a substantial portion of the lactation period may not be justified. The authors compare smallholder dairy lactation curves estimated from data gathered by two studies in Kiambu District in the Kenyan highlands to determine whether estimation of lactation curves from recall data necessarily yields less useful results compared to estimation using directly recorded longitudinally-gathered data.